Thermophysical Properties of Brazilian Orange Juice as Affected by Temperature and Water Content - Telis-Romero, J. [UNESP]; Telis, V. R N [UNESP]; Gabas, A. L. [UNESP]; Yamashita, F. (Elsevier, 1998)
The specific heat, thermal conductivity, thermal diffusivity and density of Brazilian orange juice were determined between 0.34 and 0.73 (w/w) water content and with temperatures from 0.5 to 62°C. The experimental data were fitted as functions of temperature and water content and all properties showed a linear dependency with these variables. In the tested range, the water content exhibited a greater influence on the analyzed properties than temperature. © 1998 Elsevier Science Limited. All rights reserved.
Keywords: Composition effects; Density of liquids; Specific heat of liquids; Thermal conductivity of liquids; Thermal diffusion in liquids; Thermal effects; Water; Orange juice; Food products